Upstairs/downstairs revisited: spatial pretraining‐induced rescue of normal spatial learning during selective blockade of hippocampal N‐methyl‐d‐aspartate receptors. Issue 5 (21st December 2012) - Inglis, Jennifer; Martin, Stephen J.; Morris, Richard G. M.
Abstract Spatial pretraining can enable spatial learning in another environment that ordinarily requires hippocampal N‐methyl‐d‐aspartate (NMDA) receptor activity to become independent of that activity. This study explored further the circumstances in which this training‐induced 'rescue' of later learning in the presence of the NMDA receptor antagonist 2‐amino‐5‐phosphonovaleric acid (D‐AP5) can occur. D‐AP5 (0, 10, 20 and 30 mm in artificial cerebrospinal fluid) was infused continuously (0.5 μL/h, from a minipump) and bilaterally into the dorsal hippocampus during spatial‐reference‐memory training in a watermaze (4 trials/day, 8 days). This was preceded either by handling only or by identical spatial training in another watermaze in a separate laboratory with different extramaze cues. In naïve rats, D‐AP5 caused a dose‐related impairment in spatial reference memory acquisition that was significant at the lowest 5 nm/h infusion concentration. In pretrained rats, the dose–response function was shifted such that, in watermaze 2, spatial learning was normal at this low concentration, with a deficit at higher infusion concentrations. The induction of long‐term potentiation in the dentate gyrus in vivo was blocked at all D‐AP5 concentrations. Sensorimotor abnormalities sometimes seen with NMDA receptor antagonists were only apparent at the highest concentration. The implication of this paradoxical dissociation between hippocampal NMDA receptor‐dependent plasticity and spatial learning is discussed with reference to two rival hypotheses of the impact of pretraining.